The Effect of Foot Pronation on Postural Control of Body and Electrical Activity of Selected Ankle Muscles during V-Cut Motion - Zahed Mantashloo; Heydar Sadeghi; Mehdi Khaleghi Tazji (Islamic Azad University, Hamedan Branch, 2017)
Objective: Due to the disruption of the body's natural posture because of the loss of medial arch of the foot in people with foot pronation, which may change postural control of body and electrical activity of muscles during the v-cut movement, the aim of this study was to study the effect of foot pronation deformity on postural control of body and electrical activity of the ankle muscles during v-cut motion.  Methods: In this semi-experimental study, from male students of Physical Education and Sports Sciences in Kharazmi University, 15 people with pronated foot deformity and 15 normal people participated as subjects in this study. Force plate was used to measure postural control of the body. Surface electromyography signals were recorded in v-cut test using Electromyography synchronized with the force plate was run. To analyze data MATLAB software was used and to compare two groups MANOVA was performed. Results: Statistical results indicated that there was a statistically significant difference in medial- lateral direction of differences in the center of mass and center of pressure between the foot pronation (pronated) and in the normal groups during v-cut movement. However, there was not any statistically significant difference in the anterior-posterior direction between the two groups in the center of mass and center of pressure (p>.0.05). In variable of electrical muscular activity (rms activity/mvc activity) during v-cut movement in medial Gastrocnemius and Soleus muscles, a statistically significant difference was not observed between normal and pronated foot groups (p>0.05), but there was statistically significant difference in anterior Tibialis and Peroneus Longus muscles between the two group (p <0.05). conclusion: Based on the obtained results it seems that foot pronation can be regarded as a factor affecting the biomechanics of v-cut by changing postural control of body in medial-lateral direction and electrical activity of anterior Tibialis and anterior Peroneus Longus muscles during v-cut movement.